Structure of Burnout among Omani Male and Female Teachers: Invariance of Structure across Gender - Maher Abu-Hilal; Said Al dafri; Hashem Kilani (Sultan Qaboos University, 2018)
Previous studies have supported the conceptualization that burnout consists of three aspects: emotional exhaustion, depersonalization and reduced personal accomplishment. When the proposed structure of burnout was tested in several studies, these three aspects were confirmed. However, several researchers found that depersonalization consists of two factors rather than one. The first factor is related to the job, while the second factor is related to students. The original factor structure (3-factor model) and the revised structure were tested by few Arab researchers. Recently, the Maslach Burnout Inventory (MBI) has been introduced to the Omani educational setting. This study aimed to test the two structures of MBI with a representative sample of Omani teachers (N=2446). Confirmatory factor analysis (CFA) revealed that the 4-factor model was superior and more parsimonious (CFI = .919, RMSEA = .051) than the 3-factor model (CFI = .887, RMSEA = .059). Three of the four factors had a high reliability coefficient (emotional exhaustion, a = .87, personal accomplishment, a = .76, depersonalization-job, a = .79) while depersonalization of students had low reliability (a = .47). The latter seems to be culture specific.